COMPUTER-ASSISTED INSTRUCTION IN NURSING EDUCATION IN SOUTH AFRICA. - Maboe, K. A.; de Villiers, L. (Africa Journal of Nursing & Midwifery, 2011)
Nurse educators function in a post-industrial, information and communication technology driven world. They are required to equip student nurses with the competencies to render healthcare in technologically advanced healthcare settings. Modern developments in information-communication and educational technologies compel nurse educators to make a paradigm shift by redirecting the emphasis from traditional methods of instruction to computer-assisted instruction (CAI) and computer-based learning. This study investigated the nature of student nurses' exposure to CAI and computer-based learning, the perceived benefits of this exposure, as well as the challenges encountered. A quantitative, non-experimental, univariate, descriptive survey research design was utilised. The respondents comprised 172 second year and 119 third year student nurses. Although the respondents preferred CAI to traditional modes of teaching, evidence of ineffective CAI was portrayed in the findings. It is recommended that various educational computer packages that support mastery of subject content and the development of higher cognitive skills be accessed and utilised.